Identifying competing interest disclosures in systematic reviews of surgical interventions and devices: a cross-sectional survey - Yu, Jiajie (BMC Med Res Methodol, 2020)
BACKGROUND: A competing interest is an important source of bias in research and disclosure is frequently employed as a strategy to manage it. Considering the importance of systematic reviews (SRs) and the varying prevalence of competing interests in different research fields, we conducted a survey to identify the range of competing interests in SRs assessing surgical interventions or devices and explored the association between the competing interest disclosures and authors’ conclusions. METHODS: We retrieved SRs of surgical interventions and devices published in 2017 via PubMed. Information regarding general characteristics, funding sources, and competing interest disclosures were extracted. We conducted a descriptive analysis of the studies’ characteristics and compared them between Cochrane SRs (CSRs) and non-Cochrane SRs using the Chi-square test. Results were expressed as odds ratio and their 95% confidence interval. RESULTS: One hundred fifty-five SRs published in 2017 were included in the study. More than half of the SRs (58.7%) reported their funding sources and 94.2% reported authors’ competing interest disclosures. Among 146 SRs that stated competing interest disclosures, only 35 (22.6%) SRs declared at least one author had a competing interest. More than 40 terms were used to describe competing interests. Cochrane SRs (CSRs) were more likely to provide a detailed description of competing interests compared to those in non-CSRs (48.0% versus 25.4%, P = 0.023). No association between positive conclusions and competing interest disclosures was found (P = 0.484, OR = 0.43, 95%CI: 0.08, 2.16). In the subgroup analyses, SRs stating no competing interest disclosure were more likely to report positive conclusions than those stating at least one type of competing interest, but the difference is not significantly different (P = 0.406, OR = 1.38, 95%CI: 0.64, 2.98). CONCLUSION: In surgical SRs, there is a high percentage of competing interest disclosures but without detailed information. The identification and statement of competing interests with a detailed description, particularly the non-financial ones, needs improvement. Some efficient and effective methods/tools for identifying, quantifying, and minimizing potential competing interests in systematic reviews remains valuable.